Maternal depression, antidepressant prescriptions, and congenital anomaly risk in offspring: a population-based cohort study - Ban, Lu; Gibson, Jack E.; West, Joe; Fiaschi, Linda; Sokal, Rachel; Smeeth, Liam; Doyle, P.; Hubbard, Richard B.; Tata, Laila J. (Wiley, 2014)
OBJECTIVE: To estimate risks of major congenital anomaly (MCA) among children of mothers prescribed antidepressants during early pregnancy or diagnosed with depression but without antidepressant prescriptions. DESIGN: Population-based cohort study.